Asuhan Akupunktur Pada Penderita Radang Amandel Kronis di Penyehat Klasik Ummu Aufa Kota Batam - Dede Neulis Martini; Amal Prihantono; Puspo Wardoyo (Jurnal Sosial Teknologi, 2026)
This research focuses on acupuncture care for chronic tonsillitis patients at Penyehat Klasik Ummu Aufa in Batam. Chronic tonsillitis, a recurrent infection of the palatine tonsils, results in persistent sore throat, difficulty swallowing, and bad breath. The study aims to assess the efficacy of acupuncture in alleviating symptoms and improving the condition of patients who have not undergone tonsillectomy. Acupuncture points such as LI-11, ST-44, and SP-9 were selected to reduce inflammation and promote healing. The results show significant improvements, including reduced pain, decreased swelling, and improved sleep quality. This study supports acupuncture as a complementary therapy for chronic tonsillitis. Future research with a larger sample size is recommended to confirm these findings.